Orthodontic Approaches in the Management of Mandibular Fractures: A Scoping Review - Alessandro Polizzi; Vincenzo Ronsivalle; Antonino Lo Giudice; Gaetano Isola; Alberto Bianchi; Simona Santonocito; Rosalia Leonardi; Stefano Mummolo (MDPI AG, 2023)
Non-surgical approaches have been proposed in the management of mandibular fractures, especially in children, but there is a lack of clear guidelines on the clinical indications of conservative approaches. The aim of this scoping review is to provide the available evidence of the role of the orthodontist in the management of mandibular fractures. The PRISMA-ScR guidelines were followed to select eligible articles from the PubMed, Scopus, and Web of Science databases according to precise inclusion criteria. The research questions were formulated as follows: "what is the scientific evidence concerning the rule of orthodontists in the management of mandibular fractures" and "the preferential use of the direct bonding technique with orthodontic brackets rather than rigid arch bars"? Seventeen articles were included. Five articles presented the use of removable acrylic splints or functional appliances, six articles concerned the employment of cemented acrylic or rigid splints, and six articles described the management of mandibular fractures in adults and children using orthodontic brackets or mini-screws. Most of these techniques have been employed in children and growing subjects, while fewer data were available regarding conservative treatments in adults. Preliminary evidence suggests that condylar and some minor parasymphyseal fractures in children may be managed with conservative approaches. In adults, minor condylar and stable body mandibular fractures with minimal displacement have been reduced similarly. However, there are no sufficient elements that could suggest the preferential use of orthodontic brackets over rigid arch bars in adults. Further randomized and non-randomized clinical trials with long follow-ups will be needed to better define the clinical indications of the orthodontic approaches in the management of mandibular fractures based on severity, location, and age.